A new primer pair for barcoding of bees (Hymenoptera: Anthophila) without amplifying the orthologous coxA gene of Wolbachia bacteria - Christoph Bleidorn (BMC, 2021)
Abstract Objectives DNA barcoding became an effective method for the identification and monitoring of bees. However, standard primer pairs used for barcoding often result in (co-) amplification of bacterial endosymbionts of the genus Wolbachia, which are widespread among bee species. Here we designed a new primer pair and compared it with the performance of the standard Folmer-primers for a small sample set of bees representing the main taxonomic groups of bees. Results The newly designed primer pair (BeeCox1F1/BeeCox1R2) outperformed the standard barcoding primer (LCO1490/HCO2198). By generating barcodes for a small test set of bees we found that the new primer pair produced high-quality sequences in all cases for unambiguous species identification using BOLD. Conversely, the standard barcoding primers often co-amplified the homologous Wolbachia gene and resulted in mixed chromatogram signals. These sequences showed high similarity with the bacterial endosymbiont instead of the host.